2012
DOI: 10.1111/j.1365-2745.2012.02026.x
|View full text |Cite
|
Sign up to set email alerts
|

Which traits determine shifts in the abundance of tree species in a fire‐prone savanna?

Abstract: Summary 1.Fire is a process that shapes the structure and composition of vegetation in many regions. Species in these regions have presumably evolved life-history strategies that allow success in fire-prone environments. 2. In this study, we examine the extent to which the ecological success of savanna trees is determined by traits that enhance the capacity to tolerate fire and/or traits indicative of an ecophysiological capacity for rapid growth. We define ecological success as the relative change in stem den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 52 publications
(109 reference statements)
0
47
0
3
Order By: Relevance
“…Because of the contrasting allocation patterns, lanky plants have been hypothesized to be associated with relatively less intense fires than corky plants (Vines 1968;Gignoux, Clobert & Menaut 1997). However, while previous studies have demonstrated the importance of each strategy to fire-escape Higgins et al 2012;Lawes, Midgley & Clarke 2013), none have directly linked their success to the prevailing type of consumer control in savannas.…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations
“…Because of the contrasting allocation patterns, lanky plants have been hypothesized to be associated with relatively less intense fires than corky plants (Vines 1968;Gignoux, Clobert & Menaut 1997). However, while previous studies have demonstrated the importance of each strategy to fire-escape Higgins et al 2012;Lawes, Midgley & Clarke 2013), none have directly linked their success to the prevailing type of consumer control in savannas.…”
Section: Introductionmentioning
confidence: 87%
“…Higgins et al 2012), and there is overwhelming evidence that bark thickness is the main protective bark trait in tropical ecosystems (Pinard & Huffman 1997;Hoffmann et al 2009;Lawes et al 2011a;Brando et al 2012). Although the main path by which African savanna plants escape fire seems to be related to the lanky strategy (Lawes, Midgley & Clarke 2013), the interspecific variability of bark traits may also be important in predicting species abundances at local and regional scales (Higgins et al 2012). Differences between ecozones could have a phylogenetic basis as the two zones share very few clades (Tables S4 and S6).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…), but the concept of the fire‐resistance threshold is easily applied to height‐determined fire tolerance in African trees (see Comparison to African savannas; Higgins et al. , ).…”
Section: Quantifying Nutrient Limitation Of Savanna–forest Biome Tranmentioning
confidence: 99%